2011
DOI: 10.5535/arm.2011.35.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Foot Deformity in Charcot Marie Tooth Disease According to Disease Severity

Abstract: ObjectiveTo investigate the characteristics of foot deformities in patients with Charcot-Marie-Tooth (CMT) disease compared with normal persons according to severity of disease.MethodSixty-two patients with CMT disease were recruited for this study. The normal control group was composed of 28 healthy people without any foot deformity. Patients were classified into a mild group and a moderate group according to the CMT neuropathy score. Ten typical radiological angles representing foot deformities such as pes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While not serving as absolute cutoffs, ranges classically associated with pes cavus include a Meary's angle >4° (convex upward) or > 18° as well as a calcaneal pitch >30° . In their study correlating radiographic angles with CMT severity, Joo and colleagues found Meary's angle to decrease and the calcaneal pitch to increase in the moderately severe CMT subgroup as compared to mild CMT and controls …”
Section: Discussionmentioning
confidence: 99%
“…While not serving as absolute cutoffs, ranges classically associated with pes cavus include a Meary's angle >4° (convex upward) or > 18° as well as a calcaneal pitch >30° . In their study correlating radiographic angles with CMT severity, Joo and colleagues found Meary's angle to decrease and the calcaneal pitch to increase in the moderately severe CMT subgroup as compared to mild CMT and controls …”
Section: Discussionmentioning
confidence: 99%
“…Many other foot deformities can arise as many patients are tested lately [4]. The study of So Young Joo et al confirms that the lateral talo-first metatarsal angle, anteroposterior talo-first metatarsal angle, lateral calcaneal-first metatarsal angle, lateral naviocuboid overlap, lateral calcaneal pitch, lateral tibiocalcaneal angle, and lateral talocalcaneal angle in the group of CMT patients showed a significant difference compared to the normal control group of healthy people [5].…”
mentioning
confidence: 87%
“…17 Objective measurements include increased Meary angle (apex superior) >4° to 5°, increased calcaneal pitch typically >30°, posterior subluxation of the fibula, and decreased Hibbs angle; on AP imaging, cavovarus deformity exemplifies increased talocalcaneal and talo-first metatarsal angles. 18,19 A cavovarus foot precorrection and postcorrection are demonstrated in Figure 13. Hindfoot alignment imaging would demonstrate worsening varus with an increased apparent moment arm medially.…”
Section: Pes Cavusmentioning
confidence: 99%